New Heterocyclic Organo-Chalcogenide Compounds: Synthesis, Physicochemical Characterization, and Evaluation of Anticancer Activity against Breast Cancer Cells - Hayat Hamza Abbas; Majeed Yacoob Al-Luaibi; Mohammed Jassem Al-Assadi (Universitas Gadjah Mada, 2023)
This work aimed to synthesize, characterize and evaluate the thermal stability of new sulfur and selenium organochalcogenide derivatives and to test the cytotoxic activity against breast adenocarcinoma cell line (MCF-7) through conducting MTT assay and AO/EB dual staining-technique. Two series of ten organo-chalcogen compounds: 4-(substituted)phenylthiomorpholine-3,5-dione and 4-(substituted)phenylselenomorpholine-3,5-dione were prepared by the reaction of Na2S·3H2O and NaHSe with N-(substituted)phenyl-2-chloro-N-(2-chloroacetyl)acetamide, respectively, under nitrogen atmosphere to give the corresponding cyclic chalcogenide ligands. All new compounds were characterized by melting point, FTIR, elemental analysis, UV-Visible, 1H-NMR and 13C-NMR. Meanwhile, TG/DTA analysis of some of these ligands was conducted to evaluate the thermal stability, kinetic, and characteristic thermodynamic parameters. Absorption spectroscopy was used to investigate these compounds with human DNA. The experimental results investigated a hypochromic effect via intercalation binding mode. The role of the prepared ligands in breast cell lines has been investigated by conducting MTT assay via spectroscopic techniques on HBL100 and MCF-7, normal and cancer breast cell lines, respectively. Cell death was seen after AO/EB dye staining method employing the fluorescence microscopy technique. The results revealed that these compounds possess cytotoxic activity on the MCF-7 and HBL-100 cell lines at a fixed concentration.